Fluctuations in the wage gap between vocational and general secondary education: lessons from Portugal - Raposo, Pedro Miguel (2022)
We document and analyse the wage gap between vocational and general secondary education in Portugal between 1994 and 2013. As Portuguese workers have been educated in different school systems, we have to distinguish between birth cohorts. Analysing the wage gaps within cohorts, we find no support for either the human capital prediction of crossing wage profiles or the hypothesis that general graduates increasingly outperform vocational graduates in late career. We discover that the life- cycle wage profiles have shifted over time. We link the pattern of shifting cohort profiles to changes in the school system and in the structure of labour demand. We conclude that assessing the relative value of vocational education requires assessing how the vocational curriculum responds to changes in economic structure and technology. We show that the decline in assortative matching between workers and firms has benefited vocationally educated workers.